Beef Supply Chain Analysis to Improve Availability and Supply Chain Value Using System Dynamics Methodology - Anaking, Purnama; Suryani, Erma (IPTEK Journal of Proceedings Series, 2020)
The research focuses on beef commodity where beef demands data continue increasing proportionate or in line with increasing population, national per capita income, and the needs of industrial foods process materials. On the other hand, domestic beef supply tends to decrease so it can’t meet domestic demand. Furthermore, there are problems with fulfilling supplies to the end customer. The effort in solving the problems by improving the supply chain process using a model-driven decision support system, to model the existing system and build new scenarios to increase beef supply chain performance. The model-driven decision support system approaches using a system dynamics model to accommodate key variables or parameters that significantly contribute to the continuity strategic beef supply chain. The results showed a policy scenario with success indicators in the form of optimizing average beef weight values to 300 kgs per cattle and with carcass percentage value at 55% life weight, projecting deficit beef values decreasing in each year. At 2027 deficit value becoming small which is 8,520 tons, which ends up becoming surplus in 2028. The results of the model-driven decision support system output scenario can be functioned as input to the decision-maker to elaborate policy process related to the beef's food sector to achieve food self-sufficiency which one of the government missions.